Alvin Ho : allergic to camping, hiking, and other natural disasters - Look, Lenore (Schwartz & Wade Books, 2009)
When Alvin's father takes him camping to instill a love of nature, like that of their home-town hero Henry David Thoreau, Alvin makes a new friend and learns that he can be brave despite his fear of everything.